Relationship between gynecological disorders and related pathological conditions in immature girl harmed due to military actions and armed conflicts - V.O. Dynnik (Zaslavsky O.Yu., 2018)
Background. Nowadays, the problem of a comprehensive approach to detecting and treatment of each patient has been again brought up to date. Modern medicine is characterized by a large number of new diagnostic techniques and a huge variety of therapeutic and prophylactic technologies. Thereby, there are a number of questions regarding the integral assessment of the patient's condition, and the development of modern rehab programs are the most important, taking into account the multidisciplinary approach. The purpose was to determine the incidence and nature of extragenital pathology in girls with disorders of menstrual function suffered from the anti-terrorism operation (ATO) area. Materials and methods. One-hundred and nine menstruating girls aged 11 to 18 years old from the ATO area underwent complex examination and treatment at various departments of the Institute for Children and Adolescents Health Care of NAMS. Results. The study showed a high incidence of endocrine, somatic, and psychiatric pathologies in girls with menstrual dysfunctions. The most commonly reported changes are the endocrine system disorders with thyroid gland pathology prevailing. Gastrointestinal tract disorders are predominant in the structure of somatic pathology. Neurotic disorders and vegetative dysfunction syndrome are predominant in the register of mental disorders. The diabetic patients undergoing treatment in the Endocrinology Department with thyroid diseases and hypothalamic-pituitary dysfunction most often required help of pediatric gynecologist. Girls with rheumatic diseases deserve special attention in the department of cardiorheumatology. Almost 40 % of them reported menstrual dysfunction. Conclusions. Taking into account the high rates of comorbidity of various endocrine, somatic, and psychiatric pathologies with gynecological disorders, the consultation of pediatric gynecologist should be included into the mandatory examination of the girls with these disorders. An interdisciplinary approach to the development of treatment and rehabilitation tactics will allow physicians to assess the severity and possible consequences of the comorbidity, provide purposeful examination of patients, increase the effectiveness of ongoing therapeutic interventions and reduce the adverse prognosis for disease.